Working on the dirty side—the ipsilateral subclavian access for temporary pacing after lead extraction. Issue 2 (4th February 2022) - Zweiker, David; Melillo, Francesco; D'Angelo, Giuseppe; Radinovic, Andrea; Marzi, Alessandra; Cianfanelli, Lorenzo; Altizio, Savino; Limite, Luca R.; Paglino, Gabriele; Frontera, Antonio; Nakajima, Kenzaburo; Brugliera, Luigia; et al.
Abstract: Background: Temporary pacing is necessary in pacemaker‐dependent patients after transvenous lead extraction (TLE) for cardiac implantable electronic device infection. In case of unavailability of other accesses, we propose to use the ipsilateral subclavian access (ISA) combined with a standard permanent active fixation lead for the temporary pacemaker and present preliminary data. Methods: We consecutively enrolled patients undergoing TLE who received a temporary pacemaker using the ISA between August 2016 and April 2020 at our centre. Results: During the observation period, 36 patients undergoing TLE for pocket infection (72.2%), endocarditis (25.0%) or other causes received a temporary pacemaker over the ISA. Their mean age was 77.0 ± 10.7 years, and 13.9% were female. Complete TLE was achieved in 94.4%. There were no major periprocedural complications. Intra‐hospital mortality was 11.1%. Pocket revision was performed in 19.4%. During long‐term follow‐up (23 ± 13 months), 8.3% had a relapse of local pocket infection and 2.8% needed rehospitalization for reintervention. Conclusions: Temporary pacing using a standard permanent active fixation lead using the ISA is a convenient alternative to conventional venous accesses. However, risks of implanting a lead into a previously infected area have to be taken into account. Abstract : We propose to use the ipsilateral subclavian access (ISA) for temporary pacing in selected pacemaker‐dependent patients undergoing transvenous lead extraction (TLE). We show a low complication rate in a retrospective single‐centre study of 36 consecutive patients using the ISA after TLE. Use of the ISA may be restricted to selected patients as there is a risk of infection recurrence.